Advantages of nitrogen fertilizer deep placement in greenhouse gas emissions and net ecosystem economic benefits from no-tillage paddy fields. (1st August 2020) - Liu, T.Q.; Li, S.H.; Guo, L.G.; Cao, C.G.; Li, C.F.; Zhai, Z.B.; Zhou, J.Y.; Mei, Y.M.; Ke, H.J.
Abstract: Unreasonable application of nitrogen (N) fertilizers gives rise to agricultural greenhouse gas (GHG) emissions, causing increases in carbon footprint (CF). To solve such problems, scholars have proposed the practice of N deep placement (DPN), which has been proven to be an effective approach to enhance N use efficiency and reduce N loss. However, the effect of DPN on CF and net ecosystem economic benefit (NEEB) from no-tillage (NT) rice fields remains largely unknown. In this work, a field experiment was conducted with a random complete block design to investigate the differences in soil CH4 and N2 O emissions, agricultural GHG emissions, grain yield, CF, and NEEB from NT paddy fields between urea deep placement (UDP) and urea broadcasting (UBC) in central China. The CF for the entire rice production chain can be calculated as the ratio of total GHG emissions to grain yield using a life-cycle approach. The novelty of this study lies in the examination of the integrated effects of DPN on GHG emissions, grain yield, CF and NEEB from NT paddy fields. The agricultural GHG emissions varied from 1297.0 to 1420.8 kg CO2 -eq ha −1 . Chemical fertilizers dominated the GHG emissions. UDP resulted in 96.8 kg CO2 -eq ha −1 more emissions than UBC due to more consumption of diesel by machinery operations. Compared with UBC, UDP significantly reduced soil CH4 emissions by 36–39% and N2 O emissions by 29–31%. The mitigation of soil CH4 and N2 O emissions under UDP decreased the total GHG emissions by 34% and CF by 46%. Soil CH4 emissions accounted for 83–88% of the total GHG emissions. The NEEB under UDP was 48% higher than that under UBC. In conclusion, DPN can increase grain yield, reduce CF, and enhance NEEB from NT rice fields, and may be an economic and cleaner approach for rice production. Graphical abstract: Changes in total greenhouse gas emissions, carbon footprint and net ecosystem economic benefit under different N fertilization methods. Image 1 Highlights: N deep placement decreased soil CH4 and N2 O emissions from no-tillage rice fields. N deep placement reduced carbon footprint compared with N broadcasting. N deep placement enhanced net ecosystem economic benefit relative to N broadcasting.